Twisting process of silk fiber

Through the twisting process and modifier treatment of silk fibers, the problem of poor mechanical properties of natural silk is solved, significantly improving the mechanical properties and moisture absorption and moisturizing properties of silk fibers, and improving the quality and performance of silk clothing.

CN116479596BActive Publication Date: 2025-02-11TOPSON TEXTILE CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310570596.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-19
Publication Date
2025-02-11
Estimated Expiration
2043-05-19

AI Technical Summary

Technical Problem

Natural silk has poor mechanical properties and is prone to breaking, resulting in waste of resources and low quality of finished products, limiting the promotion of silk clothing.

Method used

The twisting process of silk fibers is adopted, including impregnating the silk yarn in water at 90-100°C and in a 10-15% sodium hydroxide solution, followed by a modifier treatment. Modifiers include modified chitosan, sodium alginate, carbon nanotubes, nanotitanium dioxide, wheat straw, etc. Through the cross-linking and loading of these materials, the mechanical properties and moisture-absorbing and moisturizing properties of silk fibers are enhanced.

Benefits of technology

It significantly improves the mechanical properties and moisture-absorbing and moisturizing properties of silk fibers, enhances its anti-break strength and moisture-absorbing properties, and improves the quality and performance of silk clothing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004238427010000091
    Figure BDA0004238427010000091
  • Figure BDA0004238427010000101
    Figure BDA0004238427010000101
Patent Text Reader

Abstract

The present application discloses a twisting process for silk fibers, comprising the following steps: immersing silk yarn in water at a temperature of 90-100°C, then immersing in a sodium hydroxide solution having a mass concentration of 10-15%, and then immersing in a modifier to obtain treated silk yarn; the treated silk yarn is divided into two groups, one group is recorded as the first strand of silk yarn, and the other group is recorded as the second strand of silk yarn without twisting, and the first strand of silk yarn is forward twisted; the first strand of silk yarn with forward twisting and the second strand of silk yarn without twisting are twisted together to obtain silk fibers; the modifier includes the following raw materials: modified chitosan, sodium alginate, carbon nanotubes, nano titanium dioxide, wheat straw, dispersant, cross-linking agent, surfactant and deionized water. The silk fiber prepared by the present application has good mechanical properties and moisture absorption and moisture retention properties, and has good air permeability and mechanical strength when subsequently applied to fabrics.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of functional fibers, and in particular to a twisting process for silk fibers. Background Art

[0002] Silk is a continuous long fiber formed by the silk fluid secreted by mature silkworms when they make cocoons. It is a natural fiber that is soft and smooth to the touch, warm and breathable. It feels dry and cool when worn in summer and has good warmth retention in winter, making it suitable for use in clothing materials.

[0003] Silk is usually a protein fiber composed of eighteen kinds of amino acids combined in different proportions and spaces. These amino acids have many benefits to the human body. They emit a component called "sleep factor", which can make people's nerves in a more stable state, promote sleep, and bring people a comfortable sleep enjoyment. Therefore, clothes made of natural silk are widely loved by people.

[0004] However, natural silk has average mechanical properties and is prone to breakage during the textile process, resulting in a large waste of resources and low quality of the finished product, which is not conducive to the promotion of silk clothing. Summary of the invention

[0005] In order to improve the problem of poor mechanical properties of natural silk, the present application provides a twisting process for silk fibers.

[0006] The present application provides a silk fiber twisting process, which adopts the following technical solution:

[0007] The twisting process of silk fiber comprises the following steps:

[0008] (1) immersing the silk yarn in water at a temperature of 90-100° C. for 30-45 minutes, then immersing the silk yarn in a sodium hydroxide solution with a mass concentration of 10-15% for 10-30 minutes, and then immersing the silk yarn in a modifier to obtain a treated silk yarn;

[0009] (2) dividing the silk yarn treated in step (1) into two groups, one group being recorded as the first strand of silk yarn and the other group being recorded as the second strand of silk yarn without twisting, forward twisting the first strand of silk yarn with a forward twist of 80-120 strands / 10 cm; and parallel twisting the first strand of silk yarn with the second strand of silk yarn without twisting with a forward twist of 60-90 strands / 10 cm to obtain silk fibers;

[0010] The modifier comprises the following raw materials: modified chitosan, sodium alginate, carbon nanotubes, nano titanium dioxide, wheat straw, a dispersant, a crosslinking agent, a surfactant and deionized water.

[0011] By adopting the above technical scheme, the silk yarn is immersed in water at a temperature of 90-100°C, so that the sericin in the silk yarn is expanded, the crystalline regions become loose, and water molecules enter the amorphous region and the crystalline region, so that the distance between the silk molecular chains increases, and the surface area of ​​the fiber increases, which is conducive to the subsequent treatment with sodium hydroxide and modifiers. When the silk yarn is immersed in the sodium hydroxide solution, the sodium hydroxide corrodes the surface of the silk yarn, making the surface of the silk yarn rough and forming a pore structure, thereby increasing the specific surface area of ​​the silk yarn and facilitating the subsequent treatment with the modifier; in addition, the silk yarn is immersed in water at a temperature of 90-100°C to cause the sericin to swell, which is conducive to the erosion of the sodium hydroxide solution; the silk yarn treated with the modifier has good mechanical properties and moisture absorption and moisture retention properties, which is conducive to the application of silk clothing.

[0012] There are active hydroxyl and amino groups in the modified chitosan macromolecules, which have strong chemical reaction ability. Sodium alginate is a linear block copolymer with a six-membered heterocyclic ring as the structural unit. The primary amino groups on the modified chitosan molecular chain and the carboxyl groups on the sodium alginate molecular chain can form a three-dimensional network structure through the attraction of positive and negative charges. At the same time, a certain complex cross-linking is formed between the modified chitosan and sodium alginate and the macromolecular chains in the silk fiber. The carbon nanotubes are loaded in the three-dimensional network structure formed by the modified chitosan and sodium alginate, which increases the mechanical properties of the silk yarn and has good tensile properties and fracture resistance. At the same time, the carbon nanotubes have good hygroscopic properties, which are helpful for subsequent applications in clothing to increase the hygroscopicity and mechanical properties of clothing.

[0013] Nano-titanium dioxide has excellent antibacterial, anti-aging and chemical stability. Nano-titanium dioxide can be loaded on the surface of carbon nanotubes, reducing the probability of carbon nanotubes agglomeration, helping to load carbon nanotubes, increasing the specific surface area of ​​carbon nanotubes, and helping to load the carbon nanotubes loaded with nano-titanium dioxide in the three-dimensional network structure formed by the system, further increasing the mechanical properties and moisture absorption and permeability of the silk yarn; the cellulose in the wheat straw is twisted and agglomerated together to form a trunk fiber, and hemicellulose and lignin act as cross-linking agents between the trunk fibers, so that the wheat straw has good mechanical strength, thereby improving the mechanical properties of the silk yarn. At the same time, the wheat straw has good hygroscopic properties. The wheat straw after moisture absorption has a large specific surface area, which is conducive to the mixed cross-linking of nano-titanium dioxide, carbon nanotubes, modified chitosan and sodium alginate, increasing the cross-linking structure of the system, thereby increasing the mechanical properties of the system, and is subsequently applied to fabrics to increase the mechanical properties and hygroscopic properties of the fabrics.

[0014] Preferably, the modifier comprises the following raw materials in parts by weight: 15-25 parts of modified chitosan, 3-8 parts of sodium alginate, 10-18 parts of carbon nanotubes, 5-10 parts of nano titanium dioxide, 8-12 parts of wheat straw, 1-3 parts of dispersant, 2-5 parts of cross-linking agent, 3-6 parts of surfactant and 50-80 parts of deionized water.

[0015] By adopting the above technical scheme and further limiting the amount of each raw material component, silk fibers with excellent mechanical properties and hygroscopic properties are obtained. Modified chitosan and sodium alginate are mixed and cross-linked into a three-dimensional network structure, which is complexed and cross-linked with the macromolecular chains in the silk fibers. Carbon nanotubes and nano-titanium dioxide are loaded in the three-dimensional network structure formed by modified chitosan and sodium alginate, which increases the mechanical properties and hygroscopic properties of the silk yarn and has good tensile properties and fracture strength. Wheat straw has good hygroscopic properties and is mixed and cross-linked with nano-titanium dioxide, carbon nanotubes, modified chitosan and sodium alginate to increase the cross-linking structure of the system, thereby increasing the mechanical properties of the system, and is subsequently applied to fabrics to increase the mechanical properties and hygroscopic properties of the fabrics.

[0016] Preferably, the preparation method of the modified chitosan comprises the following steps:

[0017] (1) Dispersing chitosan in citric acid, stirring at a temperature of 45-55° C. for 1-2 h, then adding polyvinyl alcohol, continuing to stir for 2-3 h, and setting aside;

[0018] (2) dispersing graphene in ethanol, ultrasonicating, adding attapulgite, continuing stirring for 1-2 hours, and setting aside;

[0019] (3) Mix the chitosan treated in step (1) and the graphene treated in step (2), stir, then add tea polyphenols, continue stirring for 3-5 hours, and dry to obtain modified chitosan.

[0020] By adopting the above technical scheme, chitosan has excellent properties such as antibacterial property, non-toxicity, biocompatibility and biodegradability. Chitosan is dispersed in citric acid, and the citric acid molecules are cross-linked with the chitosan macromolecules, which improves the mechanical properties of chitosan. Heating accelerates the cross-linking speed of citric acid and chitosan, and then polyvinyl alcohol is added. The polyvinyl alcohol is further cross-linked with the chitosan molecules. The hydrogen bonding effect can promote the compatibility of the two to form an interpenetrating network structure, which further increases the mechanical properties of chitosan.

[0021] Graphene has excellent antibacterial properties, mechanical properties, moisture absorption and moisture retention properties and chemical stability. Attapulgite has a good aspect ratio and abundant internal pores. It is not only a good reinforcing material but also has flame retardant effects. It has strong water absorption and air permeability. Attapulgite is loaded on the surface of graphene, which increases the specific surface area of ​​graphene, thereby improving the mechanical properties and moisture absorption and moisture retention properties of graphene. The treated graphene and the treated chitosan are mixed, and the graphene and chitosan are cross-linked to form a three-dimensional network structure. The carboxyl groups on the graphene react with the amino groups in the chitosan structure to form covalent bonds, which helps to modify the chitosan. At the same time, chitosan can also reduce the aggregation of graphene to increase the specific surface area, and can effectively increase the active adsorption sites, thereby improving the adsorption performance, which helps the subsequent loading of tea polyphenols.

[0022] Tea polyphenols have antibacterial, anti-odor and antioxidant effects. The mixture of tea polyphenols, chitosan and citric acid increases the stability of the chitosan system. At the same time, tea polyphenols have good hygroscopic properties. The combination of tea polyphenols, chitosan and graphene has a good synergistic effect, inhibits the growth of microorganisms, increases the stability of the cross-linking structure of chitosan, and increases the mechanical properties and hygroscopic and moisturizing properties of silk fibers in the subsequent preparation of silk fibers.

[0023] Preferably, the mass ratio of chitosan, graphene and tea polyphenols is 1g:0.1-0.5mg:0.2-0.4g.

[0024] By adopting the above technical scheme, the mass ratio of chitosan, graphene and tea polyphenols is controlled within a certain range, so as to obtain silk fibers with good mechanical properties and moisture absorption and moisture retention properties. There is a synergistic effect between chitosan, graphene and tea polyphenols. Graphene and chitosan are cross-linked to form a network structure, and tea polyphenols and chitosan are cross-linked to form a stable structure, which further improves the comprehensive properties of chitosan. In the subsequent application in fabrics, the comprehensive properties of the fabrics such as mechanical properties and moisture absorption and moisture retention properties are increased.

[0025] Preferably, the dispersant is one or more of acetic acid, stearic acid and sodium stearate.

[0026] By adopting the above technical solution, the dispersant is added to reduce the probability of system agglomeration, increase the viscosity of the system solution, have better suspension properties, make the components evenly dispersed, and increase the uniformity of the system.

[0027] Preferably, the method for preparing wheat straw comprises the following steps:

[0028] (1) Crush the wheat straw and pass it through a 40-mesh sieve, then disperse it in a sodium hydroxide solution, soak it at a temperature of 75-85° C. for 1-3 hours, wash it with water until it is neutral, dry it, and set it aside;

[0029] (2) Dispersing the wheat straw treated in step (1) in water, then adding potato powder, montmorillonite and a coupling agent, stirring at a temperature of 90-95° C. for 3-5 hours, to obtain wheat straw.

[0030] By adopting the above technical scheme, the wheat straw is crushed and dispersed in the sodium hydroxide solution. The sodium hydroxide corrodes the surface of the wheat straw, opens the ester bonds of the cross-linked lignin and xylan in the wheat straw structure, and can partially dissolve the lignin and hemicellulose in the raw material, reduce the crystallinity of cellulose, and at the same time increase the specific surface area of ​​the lignin material, which is helpful for the mixing of subsequent components. Soaking at a certain temperature can further accelerate the rate of alkali treatment.

[0031] Potato powder has good antioxidant effect and water absorption capacity. Potato powder contains a large amount of fiber and starch, has high viscosity, and can be used as a thickener. Montmorillonite has strong adsorption capacity, impact resistance, fatigue resistance, dimensional stability and gas barrier properties. Montmorillonite can be loaded or inserted on the surface of wheat straw to further improve the mechanical properties of wheat straw. Potato powder has good viscosity and can then coat the wheat straw, increasing the connection between wheat straw and montmorillonite, thereby increasing the mechanical properties and moisture absorption and moisture retention of wheat straw. The coupling agent cross-links with potato powder to further increase the molecular structure of potato starch, which helps the coating performance of potato powder, thereby improving the mechanical properties and moisture absorption and moisture retention of wheat straw.

[0032] Preferably, the mass ratio of the wheat straw, potato powder and montmorillonite is 1:0.2-0.5:0.1-0.3.

[0033] By adopting the above technical scheme, the mass ratio of wheat straw, potato powder and montmorillonite is limited to obtain wheat straw with better mechanical properties and moisture absorption and moisture retention properties. The wheat straw and montmorillonite are mixed, and the potato powder is used to coat the wheat straw to further improve the mechanical properties and moisture absorption and moisture retention properties of the wheat straw. There is a synergistic effect between the wheat straw, potato powder and montmorillonite, which jointly improve the comprehensive properties of the wheat straw. The subsequent application in the modifier is conducive to the uniform mixing of the components, thereby improving the overall performance.

[0034] Preferably, the cross-linking agent is one or a combination of sodium tripolyphosphate, glutaraldehyde, and divinyl sulfone.

[0035] By adopting the above technical solution, the cross-linking agent plays a bridging role in the system, so that the molecules of each component are bonded and cross-linked to form a network or body structure, which helps to increase the structural strength of the system and subsequently improve various properties of the system.

[0036] Preferably, the surfactant is one or more of sorbitan monooleate, sodium dodecylbenzene sulfonate, and stearic acid.

[0037] By adopting the above technical solution, the surfactant has wetting and penetration effects, can significantly reduce the surface tension of water, and then manifest the wetting and penetration effect of the surfactant, and is used in the modifier to make the components mix evenly and increase the comprehensive performance of the system.

[0038] Preferably, in step (1), the temperature of immersing in the modifier is 70-90° C., and the immersion time is 20-30 min.

[0039] By adopting the above technical solution and setting a suitable immersion temperature and time, it is helpful to obtain a uniformly mixed raw material system.

[0040] In summary, this application has the following beneficial effects:

[0041] 1. In the present application, the silk yarn is immersed in water for expansion to increase the distance between the silk molecular chains, which is helpful for the subsequent treatment with sodium hydroxide and modifiers. When the silk yarn is immersed in the sodium hydroxide solution, the sodium hydroxide corrodes the surface of the silk yarn, making the surface of the silk yarn rough and forming a porous structure, which is helpful for the subsequent treatment with the modifier; the silk yarn treated with the modifier has good mechanical properties and moisture absorption and moisture retention properties, which is helpful for the application of silk clothing.

[0042] 2. In the present application, the primary amino groups on the modified chitosan molecular chain and the carboxyl groups on the sodium alginate molecular chain can form a three-dimensional network structure through the attraction of positive and negative charges. At the same time, a certain complex cross-linking is formed between the modified chitosan and sodium alginate and the macromolecular chains in the silk fiber. The carbon nanotubes are loaded in the three-dimensional network structure formed by the modified chitosan and sodium alginate, which increases the mechanical properties of the silk yarn and has good tensile properties and fracture strength. At the same time, the carbon nanotubes have good hygroscopic properties, which are helpful for subsequent applications in clothing to increase the hygroscopicity and mechanical properties of clothing.

[0043] 3. In the present application, nano-titanium dioxide can be loaded on the surface of carbon nanotubes, reducing the probability of agglomeration of carbon nanotubes, and helping the carbon nanotubes loaded with nano-titanium dioxide to be loaded in the three-dimensional network structure formed by the system, further increasing the mechanical properties and moisture absorption and permeability of the silk yarn; wheat straw has good mechanical strength and hygroscopic properties, which helps the mixed cross-linking of nano-titanium dioxide, carbon nanotubes, modified chitosan and sodium alginate, increasing the cross-linking structure of the system, and then increasing the mechanical properties of the system, which can be subsequently applied to fabrics to increase the mechanical properties and hygroscopic properties of the fabrics. DETAILED DESCRIPTION

[0044] The present application is further described in detail below with reference to the embodiments.

[0045] The raw materials used in the examples and comparative examples can all be obtained from commercial sources, wherein the dispersant is acetic acid, the cross-linking agent is sodium tripolyphosphate, and the surfactant is sorbitan monooleate.

[0046] Preparation example of modified chitosan

[0047] Preparation Example 1-1

[0048] The preparation method of modified chitosan comprises the following steps:

[0049] (1) Disperse 1.2 kg of chitosan in 2 L of 12% citric acid, stir at 50° C. for 2 h, then add 0.3 kg of polyvinyl alcohol, continue stirring for 3 h, and set aside;

[0050] (2) Dispersing graphene in 1.0 L of anhydrous ethanol, ultrasonicating for 1 h, adding 0.01 kg of attapulgite, continuing stirring for 2 h, and setting aside;

[0051] (3) Mix the chitosan treated in step (1) and the graphene treated in step (2), stir, then add tea polyphenol, continue stirring for 5 hours, and dry to obtain modified chitosan, wherein the mass ratio of chitosan, graphene and tea polyphenol is 1g:0.1mg:0.2g.

[0052] Preparation Example 1-2

[0053] The difference from Preparation Example 1-1 is that in step (2), no graphene is added.

[0054] Preparation Example 1-3

[0055] The difference from Preparation Example 1-1 is that in step (3), tea polyphenols are not added.

[0056] Preparation Example 1-4

[0057] The difference from Preparation Example 1-1 is that the mass ratio of chitosan, graphene and tea polyphenols is 1g:0.5mg:0.4g.

[0058] Preparation Example 1-5

[0059] The difference from Preparation Example 1-1 is that the mass ratio of chitosan, graphene and tea polyphenols is 1g:0.05mg:0.1g.

[0060] Preparation Example 1-6

[0061] The difference from Preparation Example 1-1 is that the mass ratio of chitosan, graphene and tea polyphenols is 1g:0.8mg:0.6g.

[0062] Preparation example of wheat straw

[0063] Preparation Example 2-1

[0064] The method for preparing wheat straw comprises the following steps:

[0065] (1) 2 kg of wheat straw was crushed and passed through a 40-mesh sieve, then dispersed in 3 L of a 10% sodium hydroxide solution, soaked at 80° C. for 3 h, washed with water until neutral, dried, and set aside;

[0066] (2) The wheat straw treated in step (1) was dispersed in 5 L of water, and then potato powder, montmorillonite and 0.03 kg of silane coupling agent were added, and stirred at 95 ° C for 4 h to obtain wheat straw, wherein the mass ratio of wheat straw, potato powder and montmorillonite was 1:0.2:0.1.

[0067] Preparation Example 2-2

[0068] The difference from Preparation Example 2-1 is that in step (2), no potato powder is added.

[0069] Preparation Example 2-3

[0070] The difference from Preparation Example 2-1 is that in step (2), no montmorillonite is added.

[0071] Preparation Example 2-4

[0072] The difference from Preparation Example 2-1 is that the mass ratio of wheat straw, potato powder and montmorillonite is 1:0.5:0.3.

[0073] Preparation Example 2-5

[0074] The difference from Preparation Example 2-1 is that the mass ratio of wheat straw, potato powder and montmorillonite is 1:0.1:0.5.

[0075] Preparation Example 2-6

[0076] The difference from Preparation Example 2-1 is that the mass ratio of wheat straw, potato powder and montmorillonite is 1:0.8:0.05.

[0077] Example

[0078] Example 1

[0079] The twisting process of silk fiber comprises the following steps:

[0080] (1) 1 kg of silk yarn is immersed in water at a temperature of 95° C. for 35 minutes, then immersed in 2 L of a sodium hydroxide solution with a mass concentration of 12% for 20 minutes, and then immersed in a modifier to obtain a treated silk yarn; wherein the temperature of the immersion in the modifier is 80° C. and the immersion time is 25 minutes;

[0081] (2) dividing the silk yarn treated in step (1) into two groups, one group being recorded as the first strand of silk yarn and the other group being recorded as the second strand of silk yarn without twisting, performing forward twisting on the first strand of silk yarn, with a forward twist of 100 strands / 10 cm; and twisting the first strand of silk yarn with the second strand of silk yarn without twisting together, with a forward twist of 80 strands / 10 cm during the twisting, to obtain silk fibers;

[0082] The modifier includes the following raw materials by weight: 20 kg of modified chitosan, 5 kg of sodium alginate, 14 kg of carbon nanotubes, 8 kg of nano titanium dioxide, 10 kg of wheat straw, 2 kg of dispersant, 3 kg of cross-linking agent, 5 kg of surfactant and 70 kg of deionized water;

[0083] The modified chitosan was prepared by using Preparation Example 1-1; and the wheat straw was prepared by using Preparation Example 2-1.

[0084] Example 2

[0085] The twisting process of silk fiber is different from that of Example 1 in that the modified chitosan is prepared using Preparation Example 1-2.

[0086] Example 3

[0087] The twisting process of silk fiber is different from that of Example 1 in that the modified chitosan is prepared using Preparation Examples 1-3.

[0088] Example 4

[0089] The twisting process of silk fiber is different from that of Example 1 in that the modified chitosan is prepared using Preparation Examples 1-4.

[0090] Example 5

[0091] The twisting process of silk fiber is different from that of Example 1 in that the modified chitosan is prepared using Preparation Examples 1-5.

[0092] Example 6

[0093] The twisting process of silk fiber is different from that of Example 1 in that the modified chitosan is prepared using Preparation Examples 1-6.

[0094] Example 7

[0095] The twisting process of silk fiber is different from that of Example 1 in that wheat straw is prepared using Preparation Example 2-2.

[0096] Example 8

[0097] The twisting process of silk fiber is different from that of Example 1 in that wheat straw is prepared using Preparation Example 2-3.

[0098] Example 9

[0099] The twisting process of silk fiber is different from that of Example 1 in that wheat straw is prepared using Preparation Examples 2-4.

[0100] Example 10

[0101] The twisting process of silk fiber is different from that of Example 1 in that wheat straw is prepared using Preparation Examples 2-5.

[0102] Embodiment 11

[0103] The twisting process of silk fiber is different from that of Example 1 in that wheat straw is prepared using Preparation Examples 2-6.

[0104] Example 12

[0105] The twisting process of silk fiber is different from that of Example 1 in that the modifier includes the following raw materials by weight: 15 kg of modified chitosan, 3 kg of sodium alginate, 10 kg of carbon nanotubes, 5 kg of nano titanium dioxide, 8 kg of wheat straw, 1 kg of dispersant, 2 kg of cross-linking agent, 6 kg of surfactant and 80 kg of deionized water.

[0106] Embodiment 13

[0107] The twisting process of silk fiber is different from that of Example 1 in that the modifier includes the following raw materials by weight: 25 kg of modified chitosan, 8 kg of sodium alginate, 18 kg of carbon nanotubes, 10 kg of nano titanium dioxide, 12 kg of wheat straw, 3 kg of dispersant, 5 kg of cross-linking agent, 3 kg of surfactant and 50 kg of deionized water.

[0108] Embodiment 14

[0109] The twisting process of silk fiber is different from that of Example 1 in that the modifier includes the following raw materials by weight: 10 kg of modified chitosan, 1 kg of sodium alginate, 6 kg of carbon nanotubes, 3 kg of nano titanium dioxide, 5 kg of wheat straw, 0.5 kg of dispersant, 7 kg of cross-linking agent, 1 kg of surfactant and 45 kg of deionized water.

[0110] Embodiment 15

[0111] The twisting process of silk fiber is different from that of Example 1 in that the modifier includes the following raw materials by weight: 30 kg of modified chitosan, 12 kg of sodium alginate, 22 kg of carbon nanotubes, 14 kg of nano titanium dioxide, 15 kg of wheat straw, 6 kg of dispersant, 1 kg of cross-linking agent, 8 kg of surfactant and 90 kg of deionized water.

[0112] Comparative Example

[0113] Comparative Example 1

[0114] The twisting process of silk fibers is different from that of Example 1 in that no modifier is added.

[0115] Comparative Example 2

[0116] The twisting process of silk fibers is different from that of Example 1 in that an equal amount of chitosan is used instead of modified chitosan.

[0117] Comparative Example 3

[0118] The twisting process of silk fibers is different from that of Example 1 in that carbon nanotubes are not added.

[0119] Comparative Example 4

[0120] The twisting process of silk fibers is different from that of Example 1 in that nano titanium dioxide is not added.

[0121] Comparative Example 5

[0122] The twisting process of silk fibers is different from that of Example 1 in that wheat straw is not added.

[0123] Performance testing

[0124] The silk fibers prepared in Examples 1-15 and Comparative Examples 1-5 were tested for mechanical properties and moisture absorption and air permeability;

[0125] Among them, mechanical properties test: silk fiber breaking strength and breaking elongation refer to GB / T 9997-1988 "Determination of breaking strength and breaking elongation of chemical fiber single fiber" using LLY-06E electronic single fiber strength tester to test the mechanical properties of silk fiber;

[0126] Moisture retention index: The silk fibers obtained in the embodiments and comparative examples were blended with polyester fibers to obtain fabrics, and the moisture retention index of the fabrics was tested. The moisture retention of the fabrics can be measured by moisture regain, which refers to the percentage of the weight of water contained in the fiber material to the dry weight of the fiber, with reference to the national standard GB9994-2008 "Official Moisture Regain of Textile Materials".

[0127] Determination of water absorption rate: Take the silk fiber obtained in the embodiment and the comparative example, weigh its mass and record the data m1, then immerse it vertically in a beaker container filled with deionized water. After 1 minute, take it out with tweezers and absorb the moisture on the surface around the silk fiber, and immediately weigh it and record the data m2, and calculate the water absorption rate of the silk fiber according to the following formula.

[0128] Water absorption (%) = (m2-m1) / m1×100%;

[0129] The results are shown in Table 1.

[0130] Table 1 Test data of embodiments and comparative examples

[0131]

[0132]

[0133] As can be seen from Table 1, the silk fibers prepared in Examples 1, 4, 9 and 12-13 of the present application have good mechanical properties and moisture absorption and moisture retention properties, the tensile breaking strength reaches 5.6 dN / tex, the elongation at break reaches 145%, the moisture regain reaches 16.5%, and the water absorption rate reaches 45%, indicating that the silk fibers prepared by the preparation process of the present application have excellent mechanical properties and moisture absorption and moisture retention properties, and are subsequently used in the preparation of fabrics with good air permeability and tensile strength, which contributes to comfortable wearing.

[0134] In Example 2, no graphene is added to the modified chitosan, and in Example 3, no tea polyphenols are added to the modified chitosan. As can be seen from Table 1, the tensile breaking strength is about 4.7 dN / tex, the elongation at break is about 126%, the moisture regain is about 12.9%, and the water absorption is about 35%, which shows that graphene has excellent mechanical properties, moisture absorption and moisturizing properties and chemical stability. Not adding graphene will affect the corresponding properties of silk fibers. Tea polyphenols have antioxidant effects and hygroscopic properties. Similarly, not adding tea polyphenols will affect the corresponding properties of silk fibers.

[0135] Example 5-6 changes the mass ratio of chitosan, graphene and tea polyphenols. Compared with Examples 1-4, the test data of mechanical properties and moisture absorption and moisture retention properties of the prepared silk fibers are better than those of Examples 2-3, but worse than those of Examples 1 and 4, indicating that the combination of tea polyphenols, chitosan and graphene has a good synergistic effect, inhibits the growth of microorganisms, increases the stability of the cross-linking structure of chitosan, and increases the mechanical properties and moisture absorption and moisture retention properties of silk fibers in the subsequent preparation of silk fibers.

[0136] In Example 7, no potato powder is added to the wheat straw, and in Example 8, no montmorillonite is added to the wheat straw. As can be seen from Table 1, the tensile breaking strength is about 4.6 dN / tex, the elongation at break is about 124%, the moisture regain is about 12.0%, and the water absorption is about 32%, indicating that the potato powder has good antioxidant effect and water absorption capacity, and not adding potato powder affects the comprehensive properties of the silk fiber. Montmorillonite has strong adsorption capacity and impact resistance, and not adding montmorillonite also affects the corresponding properties of the silk fiber.

[0137] In Examples 10-11, the mass ratio of wheat straw, potato powder and montmorillonite is changed. Compared with Examples 1 and 7-9, the mechanical properties and moisture absorption and moisture retention performance test data of the prepared silk fibers are better than those of Examples 7-8, but worse than those of Examples 1 and 9, indicating that there is a synergistic effect between wheat straw, potato powder and montmorillonite, which jointly improve the comprehensive properties of wheat straw. The subsequent application in the modifier is conducive to the uniform mixing of the components, thereby improving the overall performance.

[0138] Examples 14-15 change the amount of each raw material component in the modifier. As can be seen from Table 1, compared with Example 1, the tensile breaking strength is about 4.4 dN / tex, the elongation at break is about 122%, the regain is about 11.5%, and the water absorption is about 30%. The tensile breaking strength, elongation at break and moisture absorption and retention rate are greatly reduced, indicating that the raw material components are matched according to a certain content ratio so that the silk fiber has better mechanical strength and air permeability, and the change in the amount of each raw material affects the comprehensive properties of the silk fiber such as mechanical properties and moisture absorption and retention.

[0139] In Comparative Example 1, no modifier is added. As can be seen from Table 1, the tensile breaking strength is 3.2 dN / tex, the elongation at break is 60%, the moisture regain is 8.6%, and the water absorption is 15%, indicating that the addition of the modifier has a good treatment effect on the silk yarn, and improves the mechanical properties and moisture absorption and moisture retention properties of the silk fiber; in Comparative Example 2, an equal amount of chitosan is used instead of the modified chitosan. Data testing shows that the tensile breaking strength is 4.3 dN / tex, the elongation at break is 120%, the moisture regain is 11.2%, and the water absorption is 29%, indicating that the chitosan prepared in the present application has good hygroscopic and mechanical properties, which is helpful to subsequently improve the hygroscopic and mechanical properties of the silk fiber.

[0140] In Comparative Example 3, no carbon nanotubes are added to the modifier. As can be seen from Table 1, the tensile strength at break is 4.1 dN / tex, the elongation at break is 90%, the moisture regain is 10.1%, and the water absorption is 20%, indicating that the carbon nanotubes are loaded in the three-dimensional network structure formed by the modified chitosan and sodium alginate, which increases the mechanical properties and hygroscopic properties of the silk yarn.

[0141] In Comparative Example 4, no nano-titanium dioxide is added to the modifier. Data testing shows that the tensile strength at break is 4.4 dN / tex, the elongation at break is 113%, the moisture regain is 10.2%, and the water absorption is 24%, indicating that nano-titanium dioxide can be loaded on the surface of carbon nanotubes, reducing the probability of carbon nanotube agglomeration, increasing the specific surface area of ​​carbon nanotubes, and facilitating the carbon nanotubes loaded with nano-titanium dioxide to be loaded in the three-dimensional network structure formed by the system, thereby further increasing the mechanical properties and moisture absorption and permeability of the silk yarn.

[0142] In Comparative Example 5, no wheat straw is added to the modifier. As can be seen from Table 1, the tensile breaking strength is 3.7 dN / tex, the elongation at break is 70%, the moisture regain is 9.6%, and the water absorption rate is 17%, indicating that the wheat straw has good mechanical strength and hygroscopic properties. The wheat straw after moisture absorption has a large specific surface area, which is conducive to the mixed cross-linking of nano-titanium dioxide, carbon nanotubes, modified chitosan and sodium alginate, increasing the cross-linking structure of the system, and then increasing the mechanical properties of the system. It is subsequently applied to fabrics to increase the mechanical properties and hygroscopic properties of the fabrics.

[0143] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A silk fiber twisting process, characterized in that: The following steps are involved: (1) immersing the silk yarn in water at a temperature of 90-100° C. for 30-45 minutes, then immersing the silk yarn in a sodium hydroxide solution with a mass concentration of 10-15% for 10-30 minutes, and then immersing the silk yarn in a modifier to obtain a treated silk yarn; (2) Dividing the silk yarn treated in step (1) into two groups, one group being recorded as the first strand of silk yarn and the other group being recorded as the second strand of silk yarn without twisting, forward twisting the first strand of silk yarn with a forward twist of 80-120 strands / 10 cm; and parallel twisting the first strand of silk yarn with a forward twist of 60-90 strands / 10 cm to obtain silk fibers; The modifier comprises the following raw materials: modified chitosan, sodium alginate, carbon nanotubes, nano titanium dioxide, wheat straw, dispersant, cross-linking agent, surfactant and deionized water; The preparation method of the modified chitosan comprises the following steps: (1) Disperse chitosan in citric acid, stir at 45-55°C for 1-2 hours, then add polyvinyl alcohol, continue stirring for 2-3 hours, and set aside; (2) Disperse graphene in ethanol, ultrasonicate, add attapulgite, continue stirring for 1-2 hours, and set aside; (3) mixing the chitosan treated in step (1) and the graphene treated in step (2), stirring, then adding tea polyphenols, continuing to stir for 3-5 hours, and drying to obtain modified chitosan; The method for preparing wheat straw comprises the following steps: (1) Crush the wheat straw and pass it through a 40-mesh sieve, then disperse it in a sodium hydroxide solution, soak it at 75-85°C for 1-3 hours, wash it with water until it is neutral, dry it, and set it aside; (2) The wheat straw treated in step (1) is dispersed in water, and then potato powder, montmorillonite and a coupling agent are added, and stirred at a temperature of 90-95° C. for 3-5 hours to obtain wheat straw.

2. The twisting process of silk fiber according to claim 1, characterized in that: The modifier comprises the following raw materials in parts by weight: 15-25 parts of modified chitosan, 3-8 parts of sodium alginate, 10-18 parts of carbon nanotubes, 5-10 parts of nano titanium dioxide, 8-12 parts of wheat straw, 1-3 parts of dispersant, 2-5 parts of crosslinking agent, 3-6 parts of surfactant and 50-80 parts of deionized water.

3. The twisting process of silk fiber according to claim 1, characterized in that: The mass ratio of the chitosan, graphene and tea polyphenols is 1g:0.1-0.5mg:0.2-0.4g.

4. The twisting process of silk fiber according to claim 1, characterized in that: The dispersant is one or more of acetic acid, stearic acid and sodium stearate.

5. The twisting process of silk fiber according to claim 1, characterized in that: The mass ratio of the wheat straw, potato powder and montmorillonite is 1:0.2-0.5:0.1-0.

3.

6. The twisting process of silk fiber according to claim 1, characterized in that: The cross-linking agent is one or a combination of sodium tripolyphosphate, glutaraldehyde and divinyl sulfone.

7. The twisting process of silk fiber according to claim 1, characterized in that: The surfactant is one or more of sorbitol monooleate, sodium dodecylbenzene sulfonate and stearic acid.

8. The silk fiber twisting process according to claim 1, characterized in that: In step (1), the temperature of immersing in the modifier is 70-90° C., and the immersion time is 20-30 min.

Citation Information

Patent Citations

  • Anti-ultraviolet ecological finishing agent for cotton fabric as well as preparation method thereof and anti-ultraviolet ecological finishing method for cotton fabric

    CN106337280A

  • Multifunctional finishing agent

    CN109457475A